2022
DOI: 10.1038/s41467-022-29750-2
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus stabilizes movements by reducing neural spike variability in monkey basal ganglia

Abstract: The subthalamic nucleus projects to the external and internal pallidum, the modulatory and output nuclei of the basal ganglia, respectively, and plays an indispensable role in controlling voluntary movements. However, the precise mechanism by which the subthalamic nucleus controls pallidal activity and movements remains elusive. Here, we utilize chemogenetics to reversibly reduce neural activity of the motor subregion of the subthalamic nucleus in three macaque monkeys (Macaca fuscata, both sexes) during a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…According to the BG model, STN, being an integral part of the indirect and hyper-indirect pathway, inhibits unwanted movements (Alexander et al, 1986; Hasegawa et al, 2022). Recent studies of the single unit activity in monkeys have suggested that the STN may stabilize movements by reducing the variability of neural activity in the globus pallidus (Hasegawa et al, 2022). In a few studies of the STN single units in patients with PD, the authors have found neurons responding to movements of the hands, feet and face in the dorsolateral part of the nucleus (Rodriguez-Oroz, 2001; Abosch et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the BG model, STN, being an integral part of the indirect and hyper-indirect pathway, inhibits unwanted movements (Alexander et al, 1986; Hasegawa et al, 2022). Recent studies of the single unit activity in monkeys have suggested that the STN may stabilize movements by reducing the variability of neural activity in the globus pallidus (Hasegawa et al, 2022). In a few studies of the STN single units in patients with PD, the authors have found neurons responding to movements of the hands, feet and face in the dorsolateral part of the nucleus (Rodriguez-Oroz, 2001; Abosch et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, tonic delayed responses indicate the contribution of the STN also to afferent motor control. These neural responses can be interpreted using a dynamic model of the basal ganglia, which predicts temporal and functional differences of the cortico-subthalamic and strio-pallido-subthalamic pathways (Nambu et al, 2002; Hasegawa et al, 2022). Moreover, recent animal studies have reported that initiation of movements may be performed primarily through parafascicular nucleus projections to STN, which were named by the authors as the superdirect pathway (Watson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BGTM loop encompasses motor areas of the cortex such as the supplementary motor area (SMA), ventral premotor cortex (PMv), and sensorimotor cortex (SMC) along with several subcortical structures-the putamen (Put), the globus pallidus (GP), and the ventrolateral nucleus of the thalamus (VL; DeLong, 1990;Hasegawa et al, 2022). The cerebellarcortical loop consists of the motor parts of the cortex (SMC or PMv) receiving projections from the anterior lobe of the cerebellum (CB) through the dentate nucleus of the cerebellum (DN) and the ventral posterior lateral (VPL) nucleus of the thalamus, while the cerebellum receives inputs from the motor cortex through the pontine nucleus (Kelly and Strick, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The subthalamic nucleus (STN), being an important part of the basal ganglia network, projects to the external and internal pallidum, the modulatory and output nuclei of the BG, respectively, and plays an indispensable role in controlling voluntary movements (Purzner et al, 2007;Bichsel et al, 2018;Hasegawa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%